Assessing the impact of business development service providers on the performance of micro and small enterprises in Mampong municipality - Osei-Asare, Isaac (2011)
A Thesis submitted to the Department of Marketing and Strategic Management, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirement for the degree of Master of Business Administration